Rancang Bangun Mesin Penghancur Buah Kelapa Sawit Kapasitas 50 Kg/Jam - Husman Husman; Sugiyanto Sugiyanto; Denny Saputra; Ridho Rosmansyah; Zulhelmi Zulhelmi (Manutech : Jurnal Teknologi Manufaktur, 2016)
The palm companies typically consist of the oil palm plantations and the palm oil mills. Besidesproduced from their own plantations, they also buy the palm oils, CPO, and the kernel (palm kernel) fromthe farmers or other processing plants. The productions of the oil palm plantations of the farmers sold tothe collectors, and the collectors sell the palm oils to a processing plant. According to the collectors, whosell the palm olis to the factory, the price is cheap though the palm oil is in a good quality. They think tocultivate oil palm themselves, but the price of oil palm processing machines cannot be reached by them.This study will make the palm fruit crushing machine capacity of 50 kg/h, which is expected to be used bythe oil palm farmers in order to increase the sales value of the plantation. The method adopted to solvethis problem is starting with the preparation of the list of requirements necessary products, manufactureand concept selection, component design, manufacturing of image detail engineering, manufacture andassembly and test tool functions. The trial results of the palm fruit crushing machine with capacity of 50kg/h can be chopping the palm fruit with a specific gravity of 0.8245kg/liter.